Maternal and perinatal mortality and morbidity associated with tuberculosis during pregnancy and the postpartum period: a systematic review and meta‐analysis. (11th November 2016) - Sobhy, S; Babiker, ZOE; Zamora, J; Khan, KS; Kunst, H
Abstract : Background: There is a dearth of data on the clinical features and outcomes of active tuberculosis (TB) in pregnancy. Studies have shown varied results and the relationship between TB and adverse pregnancy outcomes remains unclear. Objectives: We conducted a systematic review and meta‐analysis to evaluate pregnancy outcomes associated with TB. Search strategy: Major databases were searched from inception until December 2015 without restrictions using the terms: 'TB', 'pregnancy', 'maternal morbidity', 'mortality' and 'perinatal morbidity', 'mortality'. Selection criteria: We included studies that compared the outcomes of pregnant women with and without active TB. Data collection and analysis: We computed odds ratios for maternal and perinatal complications, and pooled them using a random effects model. We assessed for heterogeneity using chi‐squared tests and evaluated its magnitude using the I 2 statistic. We used the Newcastle–Ottawa scale for quality assessment. Main results: Thirteen studies, including 3384 pregnancies with active TB and 119 448 without TB were included. Compared with pregnant women without TB, pregnant women with active TB was associated with increased odds of maternal morbidity [odds ratio (OR) 2.8, 95% CI 1.7–4.6; I 2  = 60.3%], anaemia (OR 3.9, 95% CI 2.2–6.7; I 2  = 29.8%), caesarean delivery (OR 2.1, 95% CI 1.2–3.8; I 2  = 61.1%), preterm birth (OR 1.7, 95% CI 1.2–2.4; I 2  = 66.5%), low birth weight (OR 1.7, 95% CI 1.2–2.4; I 2  = 53.7%), birth asphyxia (OR 4.6, 95% CI 2.4–8.6; I 2  = 46.3), and perinatal death (OR 4.2, 95% CI 1.5–11.8; I 2  = 57.2%). Author's conclusion: Active TB in pregnancy is associated with adverse maternal and fetal outcomes. Early diagnosis of TB is important to prevent significant maternal and perinatal complications. Tweetable abstract: Active tuberculosis in pregnancy is associated with adverse maternal and perinatal outcomes. Tweetable abstract: Active tuberculosis in pregnancy is associated with adverse maternal and perinatal outcomes.